Impact of body mass index on procedural complications, procedure duration, and radiation dose in patients with atrial fibrillation undergoing radiofrequency ablation: A systematic review and meta‐analysis. Issue 10 (3rd June 2020) - Liu, Menglu; Mei, Kaibo; Liu, Xiao; Zhao, Yujie
Abstract: Background: The association of body mass index (BMI) and procedure‐related factors in patients with atrial fibrillation (AF) after radiofrequency ablation (RFA) is still unclear. Hypothesis: BMI is associated with increased the radiation dose, procedure duration, and procedural complications. Methods: Prospective studies assessing BMI and procedure duration, radiation dose, and procedural complications in patients with AF after RFA were identified through electronic searches of PubMed, Embase, and the Cochrane Library database. Results: Ten studies with 14 735 participants undergoing RFA were included. Procedure duration was significantly longer in patients with overweight or obesity than in patients with normal BMI, with a mean difference (MD) of 0.95. Patients with overweight and obesity were exposed to a larger radiation dose, with standard MD of 1.71 and 1.98, respectively. There was no significant association between overweight or obesity and the risk of procedural complications (RR of 0.91 for overweight, 1.01 for obesity, 0.89 for stage I obesity, 1.00 for stage II obesity, and 0.94 for stage III obesity). Further analysis showed there was no significant difference regarding stroke or transient ischemic attack (overweight, RR: 0.92; obesity, RR: 1.02); cardiac tamponade (overweight, RR: 0.92; obesity, RR: 1.02); groin hematoma (overweight, RR: 0.62; obesity, RR: 0.40); or pulmonary vein stenosis (overweight, RR: 0.49; obesity, RR: 0.40) among BMI groups. Conclusion: Based on available evidence, we first showed that patients with overweight/obesity undergoing RFA experienced a significantly increased procedure duration and received a larger radiation dose than patients with normal BMI; however, there was no significant difference in procedural complications between patients with overweight/obesity and patients with normal BMI.